Wheat rhizodeposition stimulates soil nitrous oxide emission and denitrifiers harboring the nosZ clade I gene. (April 2020) - Ai, Chao; Zhang, Meiling; Sun, Yuanyuan; Zhang, Liyu; Zeng, Li; Liu, Yao; Wang, Xiubin; Chai, Yanjun; He, Ping; Liang, Guoqing; Zhou, Wei
Abstract: Stimulatory effects of growing plants on nitrous oxide (N2 O) emissions have been widely reported in terrestrial ecosystems, but the potential mechanisms responsible for these effects remain unclear. This study revealed that wheat can induce a 3.5–9.2-fold increase in N2 O emissions under different soil fertility levels, and that this "plant" source of N2 O occurs in the rhizosphere. Moreover, plants induced soil niche differentiation between denitrifiers harboring the nitrous oxide reductase genes nosZ I and nosZ II. Pulse labeling of wheat demonstrated that 67% of 13 C-labeled nosZ I-type denitrifiers, but no nosZ II-type denitrifiers, were more abundant in the rhizosphere than in bulk soil. Furthermore, a higher percentage of bacterial genomes containing nitrite reductase genes was found within plant-associated nosZ I-type denitrifiers than nosZ II-type denitrifiers, favoring NO2 − to N2 O conversion. Overall, this study revealed a strong selective stimulating effect of wheat on soil denitrifiers through root-derived carbon and a key role of the nosZ I-type community in rhizosphere denitrification. Highlights: Wheat can induce a 3.5–9.2-fold increase in N2 O emissions. The "plant" source of N2 O occurs in the rhizosphere. Plants induced soil niche differentiation between nosZ I and nosZ II-type denitrifiers. 67% of 13 C-labeled nosZ I-type denitrifiers were more abundant in the rhizosphere. Plant-associated nosZ I-type denitrifiers had a high percentage of nirK or nirS genes.